Oligarchic Influence and the Crisis of Environmental Law Enforcement in Indonesia - Bagas Putra Pamungkas (JUSTISIA GLOBAL EDUKASI, 2026)
Environmental law enforcement in Indonesia continues to face significant challenges despite the existence of comprehensive legal frameworks aimed at protecting natural resources and promoting sustainable development. This study critically examines the influence of oligarchic power on the implementation and effectiveness of environmental law enforcement in Indonesia. Drawing upon the perspectives of Critical Legal Studies (CLS) and political economy, the research explores how economic and political elites shape legal institutions, regulatory processes, and enforcement practices. Using a normative-critical methodology, the study analyzes legal regulations, policy developments, and institutional dynamics related to environmental governance. The findings indicate that environmental law is frequently influenced by unequal power relations that privilege corporate and political interests over environmental protection and community rights. Regulatory capture, selective law enforcement, and institutional dependency contribute to the weakening of legal accountability mechanisms. As a result, environmental degradation often persists despite formal legal prohibitions and judicial interventions. The study further demonstrates that legal norms are not applied in a politically neutral manner but are embedded within broader structures of economic and political power. From a critical legal perspective, environmental law functions not only as a regulatory instrument but also as a site of contestation between competing social interests. The research argues that strengthening environmental justice requires institutional reforms that reduce elite influence, enhance public participation, and increase transparency in decision-making processes. The study concludes that addressing the crisis of environmental law enforcement demands a structural transformation of governance arrangements that perpetuate unequal power relations. These findings contribute to critical legal scholarship by illuminating the relationship between law, power, and environmental governance in contemporary Indonesia.